Frustrated nationalism : nationalism and national identity in the twenty-first century - Mahler, Gregory S., 1950- (SUNY series in comparative politics., 2024)
"Essays that describe the efforts of a number of groups in a variety of political settings to achieve sovereign status, or at least to obtain greater control over the policies that affect them, the strategies they employ, and their current status today"--